The Effects of High-Intensity, Short-Duration and Low-Intensity, Long-Duration Hamstrings Static Stretching on Contralateral Limb Performance - Emily J. Philpott; Mohammadmahdi Bahrami; Mahta Sardroodian; David G. Behm (MDPI AG, 2024)
Introduction: Increases in contralateral range of motion (ROM) have been shown following acute high-intensity and high-duration static stretching (SS) with no significant change in contralateral force, power, and muscle activation. There are currently no studies comparing the effects of a high-intensity, short-duration (HISD) or low-intensity, long-duration (LILD) SS on contralateral performance. Purpose: The aim of this study was to examine how HISD and LILD SS of the dominant leg hamstrings influence contralateral limb performance. Methods: Sixteen trained participants (eight females, eight males) completed three SS interventions of the dominant leg hamstrings; (1) HISD (6 × 10 s at maximal point of discomfort), (2) LILD (6 × 30 s at initial point of discomfort), and (3) control. Dominant and non-dominant ROM, maximal voluntary isometric contraction (MVIC) forces, muscle activation (electromyography (EMG)), and unilateral CMJ and DJ heights were recorded pre-test and 1 min post-test. Results: There were no significant contralateral ROM or performance changes. Following the HISD condition, the post-test ROM for the stretched leg (110.6 ± 12.6°) exceeded the pre-test (106.0 ± 9.0°) by a small magnitude effect of 4.2% (p = 0.008, d = 0.42). With LILD, the stretched leg post-test (112.2 ± 16.5°) exceeded (2.6%, p = 0.06, d = 0.18) the pre-test ROM (109.3 ± 16.2°) by a non-significant, trivial magnitude. There were large magnitude impairments, evidenced by main effects for testing time for force, instantaneous strength, and associated EMG. A significant ROM interaction (p = 0.02) showed that with LILD, the stretched leg significantly (p = 0.05) exceeded the contralateral leg by 13.4% post-test. Conclusions: The results showing no significant increase in contralateral ROM with either HISD or LILD SS, suggesting the interventions may not have been effective in promoting crossover effects.